Lava Flow Direction Analysis Based on Anisotropy of Magnetic Susceptibility and Porosity of Igneous Rock from Ijen Volcanic Complex, East Java - RAMADHANA ATARITA (NIM: 12313028), FADHLI
Anisotropy of magnetic susceptibility (AMS) has been used in various study related to rocks magnetic fabric. One of the most frequent is the interpretation of lava flow direction. Based on previous studies, there is still no generalized statement regarding of the relation between AMS and lava flow direction. Therefore, it is necessary to have another parameter that can support the interpretation of lava flow direction using AMS data. In this study, we used rock porosity image data as a secondary parameter which is generated using microcomputed tomography (μCT) method. The rocks used in this study are MR2, IJ4 and ANY3 which are lava flow type igneous rocks from Ijen Volcanic Complex, East Java, Indonesia. Each rock then prepared into three core samples. Magnetic susceptibility measurements were performed in six directions for each sample, whereas porosity imaging using μCT method was performed on one sample of each rock. The results of these methods were then combined and used in the interpretation of lava flow direction. We concluded that both parameters can be used as a guide in determining lava flow direction. In addition, this study shows a positive correlation between AMS and porosity in MR2 and IJ4. However, in ANY3 there is no significant correlation between those parameters. Keywords: